INDIVIDUAL ANTIPLATELET THERAPY IN PATIENTS WITH ATHEROSCLEROSIS OF LOWER EXTREMITIES: MYTH OR REALITY? - O. V. Sirotkina; N. A. Surint; A. A. Topanova; T. V. Vavilova (Медицинский совет, 2018)
The incidence of atherosclerosis in the arteries of the lower extremities is increasing all over the world, and studies conducted in several countries have shown that increased incidence of chronic obliterating diseases of lower extremity arteries is associated with other cardiovascular events, and with poor prognosis. The development of an algorithm for an integrated approach to treatment that will make it possible to personalize the drug therapy in this group of patients was one of the ways to improve the long-term results of reconstructive interventions on the arteries of the lower extremities. The study included 105 patients of both sexes (mean age 68 ± 1) who underwent reconstructive surgery on the arteries due to obliterating atherosclerosis of the lower extremities followed-up in the City Diagnostic Center No. 1 in St. Petersburg from 2008 until now. Before seeking treatment, all patients received acetylsalicylic acid (ASA) 100 mg per day as antiplatelet therapy.  The antiplatelet therapy was adjusted on the basis of clinical data, taking into account the laboratory and molecular genetic test results. The functional activity of platelets was monitored according to the ADP- and collagen-induced impedance aggregation indices.  Identification of genetic peculiarities of the drug metabolism and the factors that influence platelet aggregation and the simultaneous laboratory evaluation of the functional activity of platelets made it possible to achieve the stably low residual reactivity of platelets in all patients included in the study by assigning an individual regimen (ASA monotherapy, clopidogrel monotherapy, DAT) and doses (ASA 100 mg or 150 mg per day) of antiplatelet agents.